Karakteristik Bahasa Anak Sekolah Dasar Muhammadiyah II Denpasar: Kajian Morfologi - Ardhanariswari, Putri Dwi; Darma Laksana, I Ketut; Widarsini, Ni Putu N. (Humanis; Vol 22 No 4 (2018), 2018)
This research titled “The Language Characteristic of Student at Elementary School Muhammadiyah II Denpasar: Morphology Study”. The purpose of this research is to know the form and forming of word that was mastered by students of elementary school Muhammadiyah II Denpasar and the factors that influence of mastering the language. The process of collecting the data uses seeing method. The process of analysis the data uses apportion, qualitative, and quantitative method. Besides, in process of the result uses informal and formal method. The result of this research was found the form and the forming of word that was already mastered by students of elementary school Muhammadiyah II Denpasar. The form includes lexicon category, lexicon form, and boarding lexicon. In lexicon category found (1) 812 nominal, (2) 553 verbal, (3) 162 adjectives, and (4) 67 numeralias. In lexicon form found (1) 1.180 single words and (2) 1.038 complex words. Besides, the process of forming word found (1) affix includes (a) prefix {ber-}, {meng-}, {di-}, {per-}, {peng-}, {se-}, {ter-}; (b) sufixs {-an}, {-i}, {-kan}, {-nya}; (c) konfixs {ke-…-an}, {ber-…-an}, {per-…-an}, {se-…-nya}, {peng-…-an}; and (d) simulfixs {meng-…-kan}, {di-…-kan}, {memper-…-kan}, {memper-…-i}; (2) reduplication includes morfemis reduplication and fonologis reduplication; (3) composition includes nominal composition and verbal composition; and (4) abbrevation includes abbreviation, piece, acronym, and contraction. The factors that influence the process of mastering the language are internal and external factor. Internal factor includes ages, connection ability, and health. Besides, the external factor includes influent of formal and informal environment of the student.